The Use of Point of Care Ultrasound in Diagnosis of Peritonsillar Abscess - Brian Kohen; Melanie Perez; Jheanelle McKay; Rolando Zamora; Curtis Xu (POCUS Journal, 2023)
The use of point of care ultrasound (POCUS) for diagnosis and treatment of peritonsillar abscess (PTA) is increasing [1]. Proven advantages include improved diagnostic accuracy and treatment success rates as well as decreased otolaryngology consultation, computed tomography (CT) usage, return visits to the emergency department (ED), and length of stay [1]. We present a case of a patient with a PTA that was diagnosed and successfully treated utilizing POCUS, avoiding the need for otolaryngology consultation and CT.